Developmental competence of different quality bovine oocytes retrieved through ovum pick-up following in vitro maturation and fertilization. (13th July 2015) - Saini, N.; Singh, M. K.; Shah, S. M.; Singh, K. P.; Kaushik, R.; Manik, R. S.; Singla, S. K.; Palta, P.; Chauhan, M. S.
Abstract : In the present study, oocytes retrieved from cross bred Karan Fries cows by ovum pick-up technique were graded into Group 1 and Group 2, based on the morphological appearance of the individual cumulus–oocyte complexes (COCs). To analyze whether the developmental potential of the COCs bears a relation to morphological appearance, relative expression of a panel of genes associated with; (a) cumulus–oocyte interaction ( Cx43, Cx37, GDF9 and BMP15 ), (b) fertilization ( ZP2 and ZP3 ), (c) embryonic development ( HSF1, ZAR1 and bFGF ) and (d) apoptosis and survival ( BAX, BID and BCL-XL, MCL-1, respectively) was studied at two stages: germinal vesicle (GV) stage and after in vitro maturation. The competence was further corroborated by evaluating the embryonic progression of the presumed zygotes obtained from fertilization of the graded COCs. The gene expression profile and development rate in pooled A and B grade (Group 1) COCs and pooled C and D grade (Group 2) COCs were determined and compared according to the original grades. The results of the study demonstrated that the morphologically characterized Group 2 COCs showed significantly ( P <0.05) lower expression for most of the genes related to cumulus–oocyte interplay, fertilization and embryonic development, both at GV stage as well as after maturation. Group 1 COCs also showed greater expression of anti-apoptotic genes ( BCL-XL and MCL1 ) both at GV stage and after maturation, while pro-apoptotic genes ( BAX and BID ) showed significantly ( P <0.05) elevated expression in poor quality COCs at both the stages. The cleavage rate in Group 1 COCs was significantly higher than that of Group 2 (74.46±7.06 v . 31.57±5.32%). The development of the presumed zygotes in Group 2 oocytes proceeded up to 8- to 16-cell stages only, while in Group 1 it progressed up to morulae (35.38±7.11%) and blastocyst stages (9.70±3.15%), indicating their better developmental potential.